MENINGKATKAN KEMANDIRIAN ANAK USIA 2-4 TAHUN MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) BERBASIS ECO PARK DI PAUD TARBIYATUS SIBYAN - Hariyanti, Hepi Lusi; Wijaya Adi Putra; Ratnasari Dwi Ade Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve the independence of children aged 2–4 years through the implementation of an Eco Park–based Project Based Learning (PjBL) model at PAUD Tarbiyatus Sibyan. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 10 children. Data were collected through observation sheets, anecdotal records, and documentation. The indicators of independence included self-care skills, ability to choose activities, task completion, responsibility for tools and the environment, and self-confidence in participating in project activities.The results showed a gradual improvement in children’s independence. In the pre-cycle stage, only 20% of the children reached the “Developing as Expected” level. After the implementation of actions in Cycle I, this increased to 50%. By the end of Cycle II, 80% of the children had reached the “Developing as Expected” and “Very Well Developed” categories. The children demonstrated positive changes, including increased self-confidence, greater ability to initiate and complete activities independently, and stronger responsibility toward the Eco Park environment.Based on these findings, it can be concluded that the Eco Park–based Project Based Learning (PjBL) model is effective in improving the independence of children aged 2–4 years and in creating more active, meaningful, and enjoyable learning experiences at PAUD Tarbiyatus Sibyan.